Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have the an ellipse with its semi-minor axis length $x$, and semi major axis $4x$. However, it is oriented $45$ degrees from the axis (but is still centred at the origin). I want to do some work with such a shape, but don't know how to express it algebraically. What is the equation for this ellipse?

share|cite|improve this question
2  
2  
$x$ is not particularly helpful as a parameter if you also intend to use it as an equation variable – Henry Feb 11 '12 at 21:35
1  
In general, compute what you already know (say, equation of the ellipse aligned with the $x$-axis) and then apply rotation by the desired angle. Look here: en.wikipedia.org/wiki/Rotation_matrix. – user12918723509187 Feb 11 '12 at 22:01

Let's suppose it was semi-major axis $4k$ and semi-minor axis $k$ to avoid confusion.

Aligned with the axes it would be

$$\frac{x^2}{(4k)^2}+\frac{y^2}{k^2}=1$$

but you want this rotated, so replace $x$ by $\frac{x+y}{\sqrt 2}$ and $y$ by $\frac{y-x}{\sqrt 2}$ to get

$$\frac{(x+y)^2}{32k^2}+\frac{(y-x)^2}{2k^2}=1$$ which you can also write as

$$17\,{y}^{2}-30\,x\,y+17\,{x}^{2} - 32\,{k}^{2} = 0.$$

share|cite|improve this answer
    
Thanks for the answer. You're right, x was a stupid choice in variable names. How does replacing $x$ by $\frac{x+y}{\sqrt(2)}$ account for the 45 degree shift, if you don't mind me asking? :) – deod Feb 11 '12 at 21:54
1  
Instead of the axes being aligned along $x=0$ and $y=0$ they are aligned along the perpendicular $x+y=0$ and $y-x=0$, $45^\circ$ to the original axes. The $\sqrt 2$ is just a scaling factor. – Henry Feb 11 '12 at 22:11
5  
@deod: The relation of the coordinates $(x,y)$ of a point in a coordinate system and the coordinates $(x^{\prime },y^{\prime })$ of the same point in a rotated coordinated system (with the positive $x^{\prime }$- axis making an angle $\theta $ with the positive $x$ - axe) is $$x^{\prime }=x\cos \theta +y\sin \theta $$ $$y^{\prime }=y\cos \theta -x\sin \theta .$$ For $\theta =45{{}^\circ}$, $\cos \theta =\sin \theta =1/\sqrt{2}$. Then $$x^{\prime }=\frac{1}{\sqrt{2}}x+\frac{1}{\sqrt{2}}y$$ $$y^{\prime }=\frac{1}{\sqrt{2}}y-\frac{1}{\sqrt{2}}x.$$ – Américo Tavares Feb 11 '12 at 22:18

Given a center for the ellipse at $C = (x_c, y_c)$ and a line that goes through $C$ with slope $s$ through the major axis of the ellipse, its equation is given by the zeros of $L(x,y) = y - y_c - s(x - x_c)$ and the line perpendicular to it (and also passing through $C$) is given by the zeros of $l(x,y) = s(y-y_c)+(x-x_c)$. The equation of the ellipse is given by the zeros of

$$E(x,y) = L(x,y)^2/a + l(x,y)^2/b - 1$$

Requiring that the distance between the intersections of $E$ and $L$ be $2M$ identifies $$b=M^2(1+s^2)$$ and similarly, requiring that the intersections between $E$ and $l$ be separated by $2m$ identifies $$a=m^2(1 + s^2)$$ This is demonstrated in the following SymPy session:

>>> from sympy import *
>>> a, b, x, y, m, M, x_c, y_c, s = var('a,b,x,y,m,M,x_c,y_c,s')
>>> L = (y - y_c) - s*(x - x_c)
>>> l = s*(y - y_c) + (x - x_c)
>>> idiff(L, y, x) == -1/idiff(l, y, x)  # confirm they are perpendicular
True
>>> E = L**2/a + l**2/b - 1
>>> xy = (x, y)
>>> sol = solve((E, L), *xy)
>>> pts = [Point(x, y).subs(zip(xy, p)) for p in sol]
>>> solve(pts[0].distance(pts[1]) - 2*M, b)
[M**2*(s**2 + 1)]
>>> sol = solve((E, l), *xy)
>>> pts = [Point(x,y).subs(zip(xy, p)) for p in sol]
>>> solve(pts[0].distance(pts[1]) - 2*m, a)
[m**2*(s**2 + 1)]

So the general equation of the ellipse centered at $(x_c, y_c)$ whose major axis (with radius of $M$) is on a line with slope $s$, and whose minor axis has radius of $m$, is given by the solutions of: $$\frac{((y - y_c) - s(x - x_c))^2}{m^2(1 + s^2)} + \frac{(s(y - y_c) + (x - x_c))^2}{M^2(1 + s^2)} = 1$$

share|cite|improve this answer

Sorry I didn’t see this one much earlier. Your ellipse has its major axis aligned with (I’m assuming) the line $y=x$, in other words it has symmetry $x\leftrightarrow y$. This means that it has an equation of the shape $$ a(x^2+y^2) + bxy+c(x+y)=1\,, $$ and since you’ve specified that the center is at the origin, you also need $c=0$. Thus your equation will simply be $a(x^2+y^2)+bxy=1$. You say that the semimajor axis is to be $4d$ and the semiminor axis is to be $d$ in length. So the points you know to be on the ellipse are $(\frac{4d}{\sqrt2},\frac{4d}{\sqrt2})=(2\sqrt2d,2\sqrt2d)$ at the end of the major axis and $(-\frac d{\sqrt2},\frac d{\sqrt2})$ on the minor axis.

Substituting these values into the equation and solving for $a$ and $b$, you get $$ a=\frac{17}{32d^2}\,,\quad b=-\frac{15}{16d^2}\,, $$ at least if I have not made a computational error. And there’s the equation for your ellipse.

share|cite|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.